Evolution of Hypofractionated Accelerated Radiotherapy for Prostate Cancer – The Sunnybrook Experience - Musunuru, Hima Bindu; Cheung, Patrick; Loblaw, Andrew (Frontiers in Oncology, 2014)
Stereotactic ablative body radiotherapy (SABR) is a newer method of ultra hypo fractionated radiotherapy that uses combination of image-guided radiotherapy (IGRT) and intensity-modulated radiotherapy (IMRT) or volumetric modulated arc therapy (VMAT), to deliver high doses of radiation in a few fractions to a target, at the same time sparing the surrounding organs at risk (OAR). SABR is ideal for treating small volumes of disease and has been introduced in a number of disease sites including brain, lung, liver, spine, and prostate. Given the radiobiological advantages of treating prostate cancer with high doses per fraction, SABR is becoming a standard of care for low and intermediate-risk prostate cancer patients based upon the results from Sunnybrook and also the US-based prostate SABR consortium. This review examines the development of moderate and ultra hypo-fractionation schedules at the Odette Cancer centre, Sunnybrook Health Sciences. Moderate hypo-fractionation protocol was first developed in 2001 for intermediate-risk prostate cancer and from there on different treatment schedules including SABR evolved for all risk groups.